2015
DOI: 10.4162/nrp.2015.9.4.379
|View full text |Cite
|
Sign up to set email alerts
|

The interaction ofApolipoprotein A5gene promoter region T-1131C polymorphism (rs12286037) and lifestyle modification on plasma triglyceride levels in Japanese

Abstract: BACKGROUND/OBJECTIVEApolipoprotein A5 gene promoter region T-1131C polymorphism (APOA5 T-1131C) is known to be associated with elevated plasma TG levels, although little is known of the influence of the interaction between APOA5 T-1131C and lifestyle modification on TG levels. To investigate this matter, we studied APOA5 T-1131C and plasma TG levels of subjects participating in a three-month lifestyle modification program.SUBJECTS/METHODSA three-month lifestyle modification program was conducted with 297 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Gene-weight interactions have also been reported for individual SNPs, including those associated with APOA5 26,[32][33][34] , LPL 26,[35][36][37][38][39][40][41][42][43] , GCKR 26,44 , insulin receptor substrate-1 (IRS-1) 45,46 , methylenetetrahydrofolate reductase (MTHFR) 47,48 , proprotein convertase subtilisin/kexin type 9 (PCSK9) 48 , APOB 49 , APOE 50 , peroxisome proliferator-activated receptor γ 2 (PPARγ2) 51 , and patatin-like phospholipase domain-containing protein 3 gene (PNPLA3) 52 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gene-weight interactions have also been reported for individual SNPs, including those associated with APOA5 26,[32][33][34] , LPL 26,[35][36][37][38][39][40][41][42][43] , GCKR 26,44 , insulin receptor substrate-1 (IRS-1) 45,46 , methylenetetrahydrofolate reductase (MTHFR) 47,48 , proprotein convertase subtilisin/kexin type 9 (PCSK9) 48 , APOB 49 , APOE 50 , peroxisome proliferator-activated receptor γ 2 (PPARγ2) 51 , and patatin-like phospholipase domain-containing protein 3 gene (PNPLA3) 52 .…”
Section: Discussionmentioning
confidence: 95%
“…Environmental factors that distinguish higher vs. lower triglycerides (e.g., obesity, physical inactivity, smoking, alcohol, high-carbohydrate diets, T2DM) are predicted to produce different genetic estimates under quantile-dependent expressivity. Traditionally, these differences have been attributed to gene-environment interactions, where: 1) the effect of the genotype on the phenotype differs by environment [26][27][28][29][30][31][32][33][34][35][36][37][41][42][43][45][46][47][48][49][50][51][52][53][54][55][58][59][60][61][62][63][65][66][67][74][75][76][77][78][79][80] , or equivalently: 2) the effect of the environment on the phenotype differs by genotype 36,[38][39][40]44,…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a 3-month intervention consisting of diet quality improvements and regular walking in individuals with hypertriglyceridemia showed greater improvements in major allele carriers for both APOA-V and triglyceride levels compared to minor allele carriers, despite a similar degree of compliance [32]. In contrast, the aforementioned genotype effect in response to a lifestyle intervention was not observed in a Japanese cohort [33]. Collectively, these studies suggest a potential moderating effect for rs662799 on blood triglyceride levels in response to longer-term lifestyle interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This can be partly explained by the different lifestyles between Chinese men and women. It has been reported that the rs662799 polymorphism had interaction with lifestyles on the lipid levels in Asians [ 28 ]. The gender-specific effects of the rs662799 polymorphism on lipid levels were also reported in other populations.…”
Section: Discussionmentioning
confidence: 99%